Reduction of carbon tetrachloride-induced nephropathy by melatonin administration - Ogeturk, M; Kus, I; Kavakli, A; Oner, J; Kukner, A; Sarsilmaz, M (Wiley, 2005)
The aim of this study was to investigate possible protective effects of melatonin on carbon tetrachloride (CCl4)-induced renal damage in rats. A total of 24 animals were divided into three equal groups: the control rats received pure olive oil subcutaneously, rats in the second group were injected with CCl4 (0.5 ml kg(-1) s.c. in olive oil) and rats in the third group were injected with CCl4 (0.5 ml kg(-1)) plus melatonin (25 mg kg(-1), s.c. in 10% ethanol) every other day for 1 month. At the end of the experimental period, the animals were sacrificed and blood samples were collected. The kidneys were removed and weighed. Urea and creatinine levels were determined in blood samples. Histopathological examination of the kidney was performed using light microscopic methods. Administration Of CCl4 significantly increased relative kidney weight (g per 100 g body weight) and decreased serum urea levels compared to controls (p < 0.01). Melatonin treatment significantly (p < 0.01) reduced relative kidney weight, and it produced a statistically equal (p = 0.268) relative weight with the kidneys of control rats. CCl4 administration alone also caused histopathologically prominent damage in the kidney compared to the control group. Glomerular and tubular degeneration, interstitial mononuclear cell infiltration and fibrosis, vascular congestion around the tubules, and interstitial haemorrhage in perivascular areas were observed in the renal cortex and cortico-medullary border. However, the affect Of CCl4 on the medulla was limited. Melatonin provided protection against CCl4-induced renal toxicity as was evident by histopathological evaluation. In view of the present findings, it is suggested that melatonin protects kidneys against CCl4 toxicity. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: melatonin; carbon tetrachloride; nephrotoxicity; urea; creatinine; histopathology; light microscopy